PENTINGNYA PELATIHAN ADMINISTRASI BAGI KELOMPOK PEREMPUAN UMKM SUMBER REJO (PETANI TAMBAK) KELURAHAN BULAK BANTENG KECAMATAN KENJERAN KOTA SURABAYA - Sedianingsih Sedianingsih; Ida Setya Dwi Jayanti; Rahmat Yuliawan (PENGABDIAN SOSIAL, 2021)
ABSTRACT Some of the problems outlined in the management of MSMEs are administrative limitations.  The bookkeeping system is relatively simple and tends to follow standard administrative rules resulting in data not being up to date. This makes it difficult to assess the performance of micro businesses. The ability to obtain sources of funds from the low capital market also occurs due to the limitations of the administrative system. This community service aims to foster a group of fisheries business (ponds) Sumber Rejo women in order to increase business productivity and welfare of its members and help the management of good administration as information material for the group and other parties related to the group such as vusiness capital, cooperation, network, and others. Keywords:  MSMEs, Training, Administration, Bookkeeping System, Productivity, and        Welfare  ABSTRAK Beberapa permasalahan yang digarisbawahi dalam pengelolaan UMKM adalah  masalah keterbatasan administrasi. Sistem pembukuan yang relatif sederhana dan cenderung mengikuti kaidah administrasi standar mengakibatkan data tidak up to date. Hal tersebut mengakibatkan sulitnya menilai kinerja usaha mikro. Kemampuan untuk memperoleh sumber dana dari pasar modal yang rendahpun juga terjadi karena keterbatasan sistem administrasi. Pengabdian kepada masyarakat ini bertujuan untuk membina kelompok usaha perikanan (tambak) perempuan Sumber Rejo agar dapat meningkatkan produktivitas usaha dan kesejahteraan anggotanya serta membantu pengelolaan administrasi yang baik sebagai bahan inform+asi bagi kelompok maupun pihak lain yang berkaitan dengan kelompok itu, seperti: usaha, permodalan, jaringan kerjasama, dan lain-lain.  Kata Kunci: UMKM, Pelatihan, Administrasi, Sistem Pembukuan, Produktivitas, dan Kesejahteraan.